ANALISIS STRUKTUR MODAL PADA PERUSAHAAN INDUSTRI SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015 - Yuliana, Septi (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims to analyze the cost of capital company and analyze the optimal capital structure of cement companies listed in the Indonesia Stock Exchange in the period 2013-2015. Method of data analysis in this research is done by doing WACC calculation, then compare it with industry average WACC value and combine it with firm value so that can be analyzed optimal capital structure in the company.From the result of this research can be known, based on calculation of weighted average cost of capital (WACC), the average WACC value at company in Cement Industry which listed in Indonesia Stock Exchange period 2013-2015 is equal to 10,41%. PT Semen Indonesia Tbk, PT Indocement Tunggal Prakarsa Tbk and PT Semen Batu Raja (Persero) Tbk have WACC value is over the industry average WACC value. While PT Holcim Indonesia Tbk has a lower WACC value compared to the industry average WACC value.Then based on WACC calculation and company value obtained result that PT Holcim Indonesia Tbk has optimum capital structure and PT Semen Batu Raja (Persero) Tbk not yet optimum. The WACC concept does not apply to PT Semen Indonesia (Persero) Tbk and PT Indocement Tunggal Prakarsa Tbk.Keywords: capital structure, firm value, cost of capital, optimal capital structure